PERMODELAN NERACA AIR DI EMBUNG OELTUA UNTUK MEMENUHI KEBUTUHAN AIR DOMESTIK DI DESA OELTUA - Dwi Ariyani; N.P Kayun (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2019)
Kupang city in East Nusa Tenggara province have dry climate and low annual rainfall. This causes required a small dam to keep water during the rainy season so it is not wasted and can be worn when the dry season arrives. One of small dam in Kupang is Oeltua Small Dam. This small dam was built in March 1997 to supply the water demands of Oeltua Villagers. Efforts to conserve water resources is intended to get enough water to supply the needs of households and farms. The review on water balance at OeltuaSmall Dam to ensure that the demand and water resources is balance. The water supply is calculated according Mock method in the period from 2007 to 2017. The maximum debit is available at 0,841 m3/second in 2012 and the minimum debit is 0,565 m 3/second in 2016. Result of analysis indicates thatthe dry years occurred in 2015, 2016 and 2017 with an average monthly debit 0.053 m 3/second. In 2015 a dry month occured in October with an inflow of 77,547.47 m3 and an outflow of 5,994.23 m3. In 2016 dry months occurred in August with an inflow of 79,908.38 m3 and an outflow of 6,910.15 m3. In 2017 the dry month occured in August with an inflow of 80,609.11 m 3 and an outflow of 9,473.17 m3. It means that in dey months the Oeltua Small Dam are still able to supply the water demands of Oeltua Villagers.